High pH-Sensitive Store-Operated Ca2+ Entry Mediated by Ca2+ Release-Activated Ca2+ Channels in Rat Odontoblasts - Kimura, Maki; Nishi, Koichi; Higashikawa, Asuka; Ohyama, Sadao; Sakurai, Kaoru; Tazaki, Masakazu; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2018)
Odontoblasts play a crucial role in dentin formation and sensory transduction following the application of stimuli to the dentin surface. Various exogenous and endogenous stimuli elicit an increase in the intracellular free calcium concentration ([Ca2+]i) in odontoblasts, which is mediated by Ca2+ release from intracellular Ca2+ stores and/or Ca2+ influx from the extracellular medium. In a previous study, we demonstrated that the depletion of Ca2+ stores in odontoblasts activated store-operated Ca2+ entry (SOCE), a Ca2+ influx pathway. However, the precise biophysical and pharmacological properties of SOCE in odontoblasts have remained unclear. In the present study, we examined the functional expression and pharmacological properties of Ca2+ release-activated Ca2+ (CRAC) channels that mediate SOCE and evaluated the alkali sensitivity of SOCE in rat odontoblasts. In the absence of extracellular Ca2+, treatment with thapsigargin (TG), a sarco/endoplasmic reticulum Ca2+-ATPase inhibitor, induced an increase in [Ca2+]i. After [Ca2+]i returned to near-resting levels, the subsequent application of 2.5 mM extracellular Ca2+ resulted in an increase in [Ca2+]i which is a typical of SOCE activation. Additionally, application of 2-methylthioadenosine diphosphate trisodium salt (2-MeSADP), a P2Y1,12,13 receptor agonist, or carbachol (CCh), a muscarinic cholinergic receptor agonist, in the absence of extracellular Ca2+, induced a transient increase in [Ca2+]i. The subsequent addition of extracellular Ca2+ resulted in significantly higher [Ca2+]i in 2-MeSADP- or CCh-treated odontoblasts than in untreated cells. SOCE, that is activated by addition of extracellular Ca2+ in the TG pretreated odontoblasts was then suppressed by Synta66, BTP2, or lanthanum, which are CRAC channel inhibitors. Treatment with an alkaline solution enhanced SOCE, while treatment with HC030031, a TRPA1 channel antagonist, inhibited it. The amplitude of SOCE at pH 9 in the presence of HC030031 was higher than that at pH 7.4 in the absence of HC030031. These findings indicate that CRAC channel-mediated alkali-sensitive SOCE occurs in odontoblasts. SOCE is mediated by P2Y and muscarinic-cholinergic receptors, which are activated by endogenous ligands in odontoblasts.